2010
DOI: 10.1097/mjt.0b013e318197eec6
|View full text |Cite|
|
Sign up to set email alerts
|

QTc Intervals in Drug Poisoning Patients with Tricyclic Antidepressants and Selective Serotonin Reuptake Inhibitors

Abstract: Commonly used agents of drug poisoning among patients who come to the emergency services are tricyclic antidepressants (TCAs). These drugs may cause defect in cardiac conduction due to the slowdown in the cardiac depolarization and expansions in the QT interval. Selective serotonin reuptake inhibitors (SSRIs) are less expansion of the QT period and lower cardio toxic side effects. The aim of this study was to investigate QTc intervals and prognosis of the patients who come to the emergency service due to TCA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Antidepressants, both selective serotonin reuptake inhibitors and tricyclic (TCA), are known to cause QTc prolongation in overdose [22]. As such, the observed increase in prolonged QTc is interesting as the number of poisonings with antidepressants was unchanged from 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Antidepressants, both selective serotonin reuptake inhibitors and tricyclic (TCA), are known to cause QTc prolongation in overdose [22]. As such, the observed increase in prolonged QTc is interesting as the number of poisonings with antidepressants was unchanged from 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Liebelt (2008) pointed to the occurrence of ECG changes both in the setting of therapeutic and toxic doses of Antipsychotics and TCAs. Several studies reported QTC prolongation and wide QRS complex were common findings in patients with TCAs or antipsychotics overdose (Açikalin et al, 2010;Khalaf et al, 2011;Saleh et al,2013 ;Karakiliç et al ,2016;Mishra &Kumar,2018) The potential mechanism underlying QT prolongation by antipsychotic drugs is based on their ability to block the rapidly activating delayed rectifier potassium current (IKr), which leads to lengthening of cardiac repolarization Regarding TCAs, they inhibit sodium channel conductance, so that phase 0 cardiac depolarization is delayed. This may cause slower conduction within the His-Purkinje fibers and ventricular myocardium, causing prolongation of the QRS complex on the ECG (Leung et al, 2012;Waring, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This finding has also been reported by other studies. These have shown a strong correlation between prescription frequency and rate of antidepressant poisoning which is more pronounced with TCAs (12,(16)(17)(18). The tricyclic antidepressant agents, particularly amitriptyline, are recognized for their potentially lethal cardiovascular and neurological effects in poisoned patients (19).…”
Section: Discussionmentioning
confidence: 99%